2020
DOI: 10.1101/2020.12.10.20245944
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Azithromycin in Hospitalised Patients with COVID-19 (RECOVERY): a randomised, controlled, open-label, platform trial

Abstract: SUMMARYBackgroundAzithromycin has been proposed as a treatment for COVID-19 on the basis of its immunomodulatory actions. We evaluated the efficacy and safety of azithromycin in hospitalised patients with COVID-19.MethodsIn this randomised, controlled, open-label, adaptive platform trial, several possible treatments were compared with usual care in patients hospitalised with COVID-19 in the UK. Eligible and consenting patients were randomly allocated to either usual standard of care alone or usual standard of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
0
17
0
6
Order By: Relevance
“…Out of these, 146 studies were further reviewed for full text and 96 eligible studies reporting 93 unique randomized clinical trials were included in the systematic review, 2, 5, 15-18, 36-125 where the RECOVERY trial was reported in four studies. 2, 15, 16, 76 Figure 1 summarizes the process of our study selection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Out of these, 146 studies were further reviewed for full text and 96 eligible studies reporting 93 unique randomized clinical trials were included in the systematic review, 2, 5, 15-18, 36-125 where the RECOVERY trial was reported in four studies. 2, 15, 16, 76 Figure 1 summarizes the process of our study selection.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 96 studies, ten were multi-arm and the rest were two-arm; 69 studies compared the investigated intervention with SOC, 19 with other active comparators and the other eight with both SOC and other interventions. About half of the studies (47/96) were of small sample size which enrolled less than 100 patients in the intention-to-treat population, seven studies recruited over 1000 patients, including four reports for the RECOVERY trial 2, 15, 16, 76 , one for the SOLIDARITY 17 trial, one for remdesivir 5 and one for baricitinib plus remdesivir 83 . Of 74 studies which recorded the baseline severity of illness, 28 involved patients mainly with severe or critical COVID-19 and 46 were mainly for mild/moderate disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, azithromycin possesses putative beneficial effects, such as antiviral and immunomodulation [11,12]. Nonetheless, large randomized clinical trials in United Kingdom and Brazil have failed to show the benefit of azithromycin in addition to standard care [13,14]. Oseltamivir was also given to this patient.…”
mentioning
confidence: 98%